AB0369 EFFICACY AND SAFETY OF RITUXIMAB ORIGINATOR AND BIOSIMILAR IN PRIMARY SJÖGREN'S SYNDROME IN A REAL-LIFE SETTING. (13th June 2020) - Carubbi, F.; Alunno, A.; Cipriani, P.; Pavlych, V.; DI Muzio, C.; Gerli, R.; Giacomelli, R.
Abstract : Background: Over the last 2 decades rituximab (RTX) has been widely used, albeit off-label, in primary Sjögren's syndrome (pSS). Several studies reported that B-lymphocyte depletion with RTX is effective in this disease not only by reducing disease activity but also by affecting the inflammation and the lymphoid organization that occur in target tissues. With the recent release of several RTX biosimilars (bRTX) on the market, the demonstration of their interchangeability with RTX originator (oRTX) is required. Objectives: To compare efficacy and safety of oRTX and bRTX in pSS patients in a real-life setting. Methods: Clinical records of pSS patients referring to a tertiary rheumatology clinic were retrospectively evaluated. Patients having received at least 2 courses of either oRTX or bRTX (1000 mg IV infusion, repeated after 2 weeks -1 course- and the course repeated after 24 weeks) with complete data at baseline and after 3, 6, 9 and 12 months of treatment were enrolled. Disease activity was assessed with the EULAR SS disease activity index (ESSDAI) and its clinical version without the biological domain (ClinESSDAI). Patient-reported symptoms were assessed with the EULAR SS Patient Reported Index (ESSPRI). Results: Seven patients that received oRTX and 7 patients that received bRTX were enrolled. Baseline clinical features, including ESSDAI and ESSPRI were similar in the 2 treatment groups. Both compounds significantly reduced ESSDAI and ESSPRI as early as 3 months and no difference between the groups was observed at any time point (Figure 1). Of interest, ESSDAI slowly decreased until month 6 when the most pronounced reduction was observed. Conversely, ESSPRI dropped to its lowest values already at month 3. With regard to safety, at 12 months of follow-up no adverse event was observed in any of the treatment groups. Conclusion: At 12 months of follow-up, oRTX and bRTX display similar efficacy and safety profiles. The improvement of patient reported outcomes is faster than the improvement of disease activity with both compounds. Our data support interchangeability of oRTX and bRTX in pSS. References: [1]Carubbi F et al. Arthritis Res Ther. 2013;15(5):R172 [2]Carubbi F et al. Lupus. 2014;23(13):1337-49 Figure 1 ESSDAI and ESSPRI values at every time point in the 2 treatment groups. Asterisks indicate p values <0.05 compared to the other treatment group at the same time point Disclosure of Interests: Francesco Carubbi Speakers bureau: Francesco Carubbi received speaker honoraria from Abbvie and Celgene outside this work., Alessia Alunno: None declared, Paola Cipriani Grant/research support from: Actelion, Pfizer, Speakers bureau: Actelion, Pfizer, Viktoriya Pavlych: None declared, claudia di muzio: None declared, Roberto Gerli: None declared, Roberto Giacomelli Grant/research support from: Actelion, Pfizer, Speakers bureau: Abbvie, Roche, Actelion, BMS, MSD, Ely Lilly, SOBI, Pfizer